Exposer une revue : l’exemple de Réalités (1946-1964). Maison européenne de la photographie (Paris), 16 janvier – 30 mars 2008 - Anne de Mondenard (In Situ)
The ambition of this article is to take a retrospective look at the exhibition ‘Réalités, an illustrated French monthly (1946-1978)’, put on at the Maison européenne de la photographie in Paris in 2008. Réalités, founded in 1946, was a monthly news magazine which ceased publication in 1978. Largely forgotten today, it was nonetheless one of the most innovatory and influential reviews of the 1950s and 1960s with circulation figures which placed it amongst the magazines which were the most read, and looked at, in France. The magazine gave ever-increasing importance to the place of photography, recruiting photographers like Édouard Boubat and Jean-Philippe Charbonnier and publishing the work of other talented photographers such as Haas, Penn or Avedon. The aim of the exhibition was to show the importance of photography in the magazine during its heyday, from 1946 to 1964. Two artistic directors were important during these years, Albert Gilou (1950-1961) and his assistant Jacques Dumons (1961-1964). In 1965, for economic reasons, the magazine changed its format and, visually, became less interesting. The exhibition did not show prints of the photos that were published in the magazine, but the photos as they were actually printed and placed in the layout of the magazine’s pages, drawing attention to covers, to illustrated articles or to double-page photo spreads. The exhibition was organised and presented in as attractive a way as possible.